Regiment piechoty Feliksa Kazimierza Potockiego, wojewody krakowskiego i chorągiew pancerna Aleksandra Łaszcza, starosty grabowieckiego w roku 1685 - Kołodziej, Robert (Verba volant, scripta manent: Księga jubileuszowa dedykowana Profesorowi Zbigniewowi Anusikowi w sześćdziesiątą piątą rocznicę urodzin, 2022)
The purpose of this publication is to present two historical sources – registers of soldiers from the time of the Polish-Turkish war in the year 1685. The first is a register of a Cracow woiwode Feliks Kazimierz Potocki’s infantry regiment (380 people), and the second – a register of starosta of Grabowiec Aleksander Łaszcz’s calvary squad (“chorągiew pancerna”, 100 horses). The lists include first and last names of officers and soldiers. Both documents are in court book (księga grodzka) of Bełz, that is in Central State Historical Archive of Ukraine in Lviv.